PKB a aktywność ekonomiczna oraz wzrost gospodarczy - Machaj, Mateusz; Lewiński, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article attempts to present a neglected feature of Gross Domestic Product. Our thesis is that the GDP is not a proper way to portray economic activity with its relation to unemployment. We also believe that GDP is not an appropriate measure to indicate economic growth
Keywords: Produkt Krajowy Brutto; PKB; działalność gospodarcza; wzrost gospodarczy; wskaźniki ekonomiczne; teoria ekonomiczna; agregaty ekonomiczne; krytyka; wydatki publiczne; ekonomia keynesowska; konsumpcja